Travel Channel Meets Discovery Channel or How Tourism Can Encourage Better Export Performance and Diversification in Nepal - Reis, José Guilherme; Varela, Gonzalo (World Bank, Washington, DC, 2014)
Entering and successfully surviving in export markets is a costly process for firms. The process involves learning about the existence of foreign demand, "discovering" production costs of exportable goods, building up reputation, succeeding in product branding to reduce competitive pressures and to be constantly upgrading quality standards to better serve demanding international clients, and remaining competitive vis-à-vis other players in the global marketplace. This paper argues that tourism can help alleviate some of these costs by providing a relatively inexpensive platform for cost-discovery and by acting as a low-cost "in-house" trade fair, accessible to all domestic producers. The analysis combines product-level data on world and Nepal's exports (both for goods that are related and unrelated to tourism) with Nepalese data on tourist inflows and expenditures and macro indicators on relative prices. For tourism-related goods, the analysis reveals a positive association between tourist inflows from given destinations and their expenditures, with future merchandise exports to those destinations. Instead, for goods a priori unrelated to tourism, the data reveal no connection between tourism flows and future exports. The results suggest spillovers from tourism into merchandise export performance and diversification and would imply that there are gains from cooperation between tourism and export promotion agencies.